2012
DOI: 10.1002/pd.3972
|View full text |Cite
|
Sign up to set email alerts
|

Fast protocol for the diagnosis of lysosomal diseases in nonimmune hydrops fetalis

Abstract: Objective Nonimmune hydrops fetalis (NIHF) is defined by the excessive fluid accumulation in more than one foetal compartments and body cavities because of nonimmune reasons. It has been described that 14 lysosomal diseases may be causative of NIHF. The aim of this study was to design a fast protocol to investigate the most frequent lysosomal diseases that are reported that may cause NIHF.Method We analysed the glycosaminoglycans excretion in the amniotic fluid supernatant and four different lysosomal enzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Noonan syndrome). Sequential protocols for investigation of NIFH have been proposed to optimize diagnosis and avoid cost prohibitive investigations . Despite these efforts, such protocols are not universally practiced.…”
mentioning
confidence: 97%
“…Noonan syndrome). Sequential protocols for investigation of NIFH have been proposed to optimize diagnosis and avoid cost prohibitive investigations . Despite these efforts, such protocols are not universally practiced.…”
mentioning
confidence: 97%
“…Gaber KR et al reported MPS II with 2-DE on the AMF in a case with high maternal serum α-fetoprotein (3.6 MoM), and neural tube defect [19]. Fetal hydrops is a manifestation in some types of MPS especially in MPS VII [20,21]. Nasr et al reported the sensitiveness of 2-DE on the Egyptian population for the PND of MPS [22].…”
Section: Discussionmentioning
confidence: 98%
“…The analytical method employed in the current study is simple, rapid, and has been found completely reliable in the prenatal diagnosis. In pregnancies with high serum α-fetoprotein and neural tube defect, AMF GAG estimation is recommended [18][19][20][21]. Patients affected with Hunter syndrome and closed cephalocele were generally overlooked in the fetal ultrasound evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, despite this there are many families have had more than one child with fetal or neonatal hydrops in whom the underlying genetic defect could not be discovered.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The identification of a single gene disorder not only helps in predicting the outcome of the current pregnancy, but also has an impact on the management or screening of future pregnancies in the family.…”
Section: Discussionmentioning
confidence: 99%